2021
DOI: 10.21203/rs.3.rs-244278/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Italian individual-level data study investigating on the association between air pollution exposure and Covid-19 severity in primary-care setting

Abstract: BACKGROUND: Several studies have been focusing on the potential role of atmospheric pollutants in the diffusion and impact on health of Covid-19. This study’s objective was to estimate the association between ≤10 micrometers diameter particulate matter (PM10) exposure and the likelihood of experiencing pneumonia due to Covid-19 using individual-level data in Italy.METHODS: Information on Covid-19 patients was retrieved from the Italian IQVIA® Longitudinal Patient Database (LPD), a computerized network of gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Daily residential air quality data at the census tract level was further averaged to assign exposure levels during shorter- and longer-term periods prior to the month of COVID-19 diagnosis. 1-month averaged exposures were used as representative of shorter-term exposure ( Chen et al, 2016 ; Fouladi et al, 2020 ; Pegoraro et al, 2021 ) and 1-year averaged exposures were used as longer-term exposures.…”
Section: Methodsmentioning
confidence: 99%
“…Daily residential air quality data at the census tract level was further averaged to assign exposure levels during shorter- and longer-term periods prior to the month of COVID-19 diagnosis. 1-month averaged exposures were used as representative of shorter-term exposure ( Chen et al, 2016 ; Fouladi et al, 2020 ; Pegoraro et al, 2021 ) and 1-year averaged exposures were used as longer-term exposures.…”
Section: Methodsmentioning
confidence: 99%
“… Pegoraro et al (2021) , citing Setti et al (2020a , c) [47,26] and Martelletti L, Martelletti P [5]: “One of the ideas underneath the potential relationship between airborne PM and Covid-19 diffusion is that the atmospheric PM might exercise a carrier action along with the virus [5, 26]. Setti and colleagues recently demonstrated the presence of the SARS-CoV-2 RNA on PM [47].”…”
Section: Citation Networkmentioning
confidence: 99%
“…54 were involved in spreading the misconception ( Al Huraimel et al, 2020 ; Amoatey et al, 2020 ; Arslan et al, 2020 ; Baron, 2021 ; Borak, 2020 ; Cao et al, 2021 ; Carraturo et al, 2020 ; Chen et al, 2021 ; Coccia, 2020a , b ; Comunian et al, 2020 ; Copat et al, 2020 ; Dettori et al, 2020 ; Domingo and Rovira, 2020 ; Dunker et al, 2021 ; Gaddi and Capello, 2020 ; He and Han, 2021 ; Ho et al, 2021 ; Ingram et al, 2021 ; Kayalar et al, 2021 ; Kumar et al, 2021 ; Linillos-Pradillo et al, 2021 ; Lorenzo et al, 2021 ; Maleki et al, 2021 ; Marquès et al, 2021 ; Martelletti and Martelletti, 2020 ; Mehmood et al, 2021 ; Mukherjee et al, 2021 ; Nor et al, 2021 ; Pegoraro et al, 2021 ; Poyraz et al, 2021 ; Prather et al, 2020 ; Qu et al, 2020 ; Ram et al, 2021 ; Sanità di Toppi et al, 2020 ; Shao et al, 2021 ; Sharma et al, 2020 ; Senatore et al, 2021 ; Setti et al, 2020a -f; Tang et al, 2020 ; Trancossi et al, 2021 ; Tretiakow et al, 2021 ; Tung et al, 2021 ; van der Valk and In 't Veen, 2021 ; Varotsos et al, 2021 ; Wang et al, 2020a , b ; Xu et al, 2020 ; Zhang et al, 2020a , c ; Zhu et al, 2021 ; Zoran et al, 2020 );…”
Section: Citation Networkmentioning
confidence: 99%
“…By analyzing the regional trends one by one, it can be observed that the "byoblu" web interest has increased over time except for Basilicata and Molise (Figure 2). Although a growing trend was already present, the novel coronavirus seems to have strongly impacted RSVs in Campania (𝛥 20…”
Section: Web Interest In Pre-existing Fake Newsmentioning
confidence: 99%
“…Conspiracy hypotheses, inadequate risk perception, and unjustified fears have already undermined non-pharmacological containment measures and can reduce the effectiveness of pharmacological ones [18]. Furthermore, these factors can compromise the management of equally serious problems such as pollution and climate change (often linked to COVID-19 incidence and mortality) [19][20][21]. Therefore, such a scenario requires careful surveillance of the online information flow as well as thoughtful communication.…”
Section: Introductionmentioning
confidence: 99%